Elastic Optical Networking in the Microsoft Cloud - Filer, Mark; Gaudette, Jamie; Ghobadi, Manya; Mahajan, Ratul; Issenhuth, Tom; Klinkers, Buddy; Cox, Jeff (Journal of Optical Communications and Networking, 2016)
To keep pace with the tremendous bandwidth growth in cloud networking, web-scale providers, such as Microsoft, have been quick to adopt elastic features of modern optical networks. In particular, colorless flexible-grid reconfigurable optical add-drop multiplexers, bandwidth-variable transceivers, and the ability to choose a variety of optical source types are integral for cloud network operators to improve network efficiency while supporting a variety of service types. We take an in-depth look at Microsoft's deployed network infrastructure and discuss the impact of elasticity on network capacity and flexibility. As a proof-of-concept, a new elastic open line system (OLS), in which the line system components and the signal sources are disaggregated, was assembled in a laboratory environment, and 4000 km of propagation over primarily nonzero dispersion-shifted fiber using multiple source types is demonstrated. Finally, the long-term goal of unifying the control plane of the OLS, DWDM signal sources, routers, and Ethernet switches under a single software-defined network controller is briefly addressed.